Case Report and Literature Review on Glycogen Hepatopathy - Ekladious, Adel (Recent Updates in Disease and Health Research Vol. 9, 2024)
This case report highlights a challenging clinical case called glycogen hepatopaty-induced acute hepatitis. This clinical condition is often underdiagnosed or misdiagnosed even by consultant specialists eventually hampering patient management and outcome. Glycogen hepatopathy is a very rare and forgotten complication of poorly controlled type 1 diabetes mellitus. Glycogen hepatopathy may also present in type II diabetes mellitus, especially when managed with high doses of insulin. Although it is a benign condition, it is rarely diagnosed in a timely manner. It is characterised by hepatomegaly causing abdominal pain due to stretch on the liver capsule causing capsulitis, and derangement of liver enzymes. We report a case of a 44-year-old male truck driver who presents to ED with right upper quadrant pain in the context of uncontrolled type II diabetes mellitus for the last two years. Glycogen hepatopathy is caused by wide fluctuations of blood glucose and treatment with large doses of insulin. High levels of insulin due to uncontrolled diabetes mellitus or high doses for treatment lead to excess glucose movement into hepatocytes via independent passive diffusion.